A Convergent Total Synthesis of 19‐Hydroxysarmentogenin1. Issue 20 (15th April 2013) - Mukai, Ken; Urabe, Daisuke; Kasuya, Satoshi; Aoki, Naoto; Inoue, Masayuki
<x xml:space="preserve">Abstract</x> 19 in 19: A convergent total synthesis of 19‐hydroxysarmentogenin has been achieved, starting from three simple fragments. The desired product was synthesized in 19 steps from the AB ring system with the installation of six stereocenters and the formation of three CC bonds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>